SPK Rekomendasi Pemilihan Kandidat Pejabat Struktural Menggunakan Metode Profile Matching (Studi Kasus: Pemerintah Kota Tarakan) - Ria Astriratma; Retantyo Wardoyo; Aina Musdholifah (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2017)
Through the State Civil Apparatus Law, the Government attempt to reduce nepotism by creating an open competition system among civil servants in the process of filling positions. Regional Civil Service Agency (BKD) Tarakan already has personnel database and decision support system that can combine the existing database with the scoring model to get the candicate profile who fit with vacant positions is needed to support more objective performance.The Application of profile matching method in this decision support system is expected to help the candidate selection process on structural officer in the Government of Tarakan comply with the ability of a required field in a position. From the research we concluded that the change in the value of the candicate profile, and the number of subcriteria that used to categorize the positions can affect the closeness of candidates with vacant position and the use of profile matching method for case that the highest value is the best value requires that the ideal value used is the value the maximum in order to avoid exceeding the expectations of ideal.